Trauma-informed care approach in developing companion robots: a preliminary observational study - Mazuz, Keren; Yamazaki, Ryuji (Frontiers in Robotics and AI, 2025)
IntroductionThis study explores the integration of Trauma-Informed Care (TIC) principles into the development of companion robots for elderly trauma survivors, particularly those with Post-Traumatic Stress Disorder (PTSD). The psychological effects of trauma, especially in aging populations, can complicate mental and physical health, highlighting the need for tailored technological solutions.MethodsThe research involved two focus groups with Holocaust survivors (N = 12) who engaged directly with a social robot. Discussions explored their needs, barriers, and coping strategies based on their longitudinal experiences of trauma, resilience, and aging. Transcripts were thematically analyzed, identifying key TIC-related themes—safety, trust, self-compassion, and self-efficacy—in relation to engagement with companion robots.ResultsFindings revealed that trauma survivors face significant challenges in communication and technology use. Safe and trusting environments were fundamental for meaningful engagement with robots. Self-compassion and self-efficacy emerged as essential to overcoming initial barriers, indicating that TIC-informed design features could facilitate better uptake and acceptance.DiscussionThe study emphasizes the importance of incorporating TIC principles to ensure these robots meet the complex needs of trauma survivors. Findings also underscore the personal histories, ongoing changes in recollecting the trauma, and the need for stable, empathetic interactions highlights the complexity of designing assistive robots for profoundly affected populations. This study contributes to digital mental health and aging technologies by emphasizing stability, empathy, and user-centered design in developing assistive robotics as a universal, scalable solution.